Evaluación de dos métodos de adiestramiento equino y su efecto en el aprendizaje - Zamora Rea, Fausto Antonio (2024)
Currently, to train a horse, methods are used that create difficulties in the cognitive capacity of the horses. The present investigation is carried out in the province of Cotopaxi, Latacunga canton. In the Salache academic experimental center with the objective of evaluating two methods of equine training and its effect on learning. In which the inductive and deductive methodology was applied from the application of the protocol to obtain cognitive results of the comparative analysis of the 2 training methods, obtaining the following results: For the degree of satisfaction of the training, the natural taming gave a result of: little satisfactory 12, satisfactory 24, very satisfactory 96. In the traditional dressage method, the result was 23 unsatisfactory, 87 satisfactory and 22 very satisfactory. With respect to training time, a significant difference was also found in natural dressage, the time was 134,672 seconds, while in traditional dressage it was 314,135 seconds. Finally, the superiority of natural dressage over traditional dressage enhances both the cognitive performance and the long-term welfare of the horses. Consequently, it is recommended that the practice of Natural Horsemanship be applied to the training of horses under the same environmental conditions.